A Sociopragmatic Study of Verbal Bullying in the Novel: “Matilda” - Al-Ani, Hani Majeed Saeed; Samir, Emad Hayif (Al-Adab Journal, 2022)
Bullying is a social phenomenon characterised by interactions that are viewed as negative, repetitive, persistent, and directed towards one or more individuals. The problem of this study is manifested in how to analyse verbal bullying linguistically, relate it to pragmatic theories, and identify some of the social scales related to it. The study aims at Describing and identifying the speech act of bullying. Identifying what impoliteness strategies and functions are employed in bullying performance. Showing the sociopragmatic factors which affect the speech act of bullying and identifying the impolite language used by those who bully. The study concluded that verbal bullying in its most basic form can be an insult that comes with an impolite function and power differences. Bullying is associated with using power to gain or increase the bully's benefits from the situation. Bullies use verbal bullying to force people to do things using their social power.